Investigation of compound flood risk under climate change: a case study of a city in Thailand - Chan, Naomi En Hui (Nanyang Technological University, 2022)
Under the effects of climate change, many coastal areas in Southeast Asia are increasingly susceptible to compound flooding. This report focuses on the city of Bang Pu, Samut Prakan, Thailand, a peri-urban area near Bangkok. The Compound Flood model developed in the SJ-NTU Corporate Lab Flood Resiliency Project was used to investigate the compound flood risk under effects of climate change and land use changes. Due to the limited information on the study area, these are the conclusions that could be made: the Compound flood risk modelled under rainfall events of 20, 50 and 100-year interval and Typhoon Linda combined with sea level rise in 2100, resulted in compound flooding of >0.1m in around a quarter of the study area. The percentage increase in total flood area between direct summation of rainfall and coastal flood and compound flood reinforces the dependency between rainfall and coastal events. The effects of change in land use on compound flood were explored as well. The comparison in compound flood risk of with and without urbanisation resulted in the increase of less than 2% of flood area. The effect of urbanisation due to increased imperviousness was thus not as great as expected. Low Impact Development (LID) controls were also modelled to show the effectiveness in mitigating compound flood and performance in a non-temperate climate area. The largest decrease in flood area was from the rainfall event of 20-year storm event, with a 15% drop. Effectiveness of LID controls was found to decrease across the time intervals as rainfall increased. Ultimately, the study of compound flood requires a multidisciplinary approach due to the interactions of different physical and anthropogenic processes.